2020
DOI: 10.1097/brs.0000000000003522
|View full text |Cite
|
Sign up to set email alerts
|

Coronal T1 Pelvic Tilt, a Novel Predictive Index for Global Coronal Alignment in Adult Spinal Deformity

Abstract: Study Design. A retrospective radiographic study. Objectives. The aim of this study was to examine the association between global coronal alignment (GCA) and L4/L5 coronal tilt, and to verify the validity of our new index for evaluating GCA. Summary of Background Data. The mechanism of coronal imbalance is still unknown. The ability to level coronal tilts of L4 and L5 has been reported to impact the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…According to previous studies [8,11] , structure curve had no in uence on coronal imbalance in ASD patients. Comparisons in this current study revealed that although the degree of the main curvatures of patients in the two groups had no difference, the involving vertebras were less in patients with coronal imbalance (group A) than those with coronal balance (group B)(t=2.639, P=0.009).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…According to previous studies [8,11] , structure curve had no in uence on coronal imbalance in ASD patients. Comparisons in this current study revealed that although the degree of the main curvatures of patients in the two groups had no difference, the involving vertebras were less in patients with coronal imbalance (group A) than those with coronal balance (group B)(t=2.639, P=0.009).…”
Section: Discussionmentioning
confidence: 81%
“…The increasing imbalance on the coronal plane in patients with degenerative lumbar scoliosis (DLS) has become one of main underlying factor that leads them to abnormal appearance, functional decline, and back pain [17] . The distance between C7 plumb line (C7PL) and central sacral vertical line (CSVL), named coronal balance difference [5] , coronal balance distance [12] , global coronal malalignment [14] , and C7 migration [11] , has been used to re ect coronal alignment. In this current study, we de ned the global coronal parameter as coronal balance distance (CBD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prior reports have outlined predictors and risk factors for postoperative CM (Table 2). First, considerable evidence from prior reports identify a positive correlation between preoperative and postoperative CM 8,16,19. Preoperative-CVA correlated with postoperative-CVA in a series of 67 ASD patients ( P <0.001)19 and a series of 121 ASD patients ( P <0.0001) 8.…”
Section: Resultsmentioning
confidence: 91%
“…The CTPT was positively correlated with CVA (termed C7 migration), with an R 2 value 0.985. 16 The authors emphasized the potential advantages of the CTPT (angle), compared with the CVA (distance), as no calibration is needed and it is not subject to body habitus variability. Lastly, additional reports have used less common composite outcomes to measure CM including T1 takeoff angle (T1-TO), shoulder tilt, and pelvic obliquity.…”
Section: Measurementsmentioning
confidence: 99%